PENGARUH PENGGUNAAN BEBERAPA PAKAN SUMBER ENERGI TERHADAP KOMPOSISI KIMIA DAGING KAMBING KACANG JANTAN YANG DIGEMUKKAN - Dominggas N. Rika; Paulus Klau Tahuk; Kristoforus W. Kia (Journal of Tropical Animal Science and Technology, 2019)
The objective of study to determine the chemical meat composition of kacang male goat fed ration with different energy sources. The livestock used were 12 male goats with an average initial body weight of 11.77 kg, ranging in age from 6 to 12 months according to dental estimates. The design used was Randomized Block Design (RBD) with 4 treatments and 3 replications. The each treatment was T0 = 80% Natural Grass + 20% Leucaena leucocephala ; T1 = 50% natural grass + 20% Leucaena leucocephala + 30% milled corn; T2 = 50% natural grass + 20% Leucaena leucocephala + 30% rice bran and T3 = 50% natural grass + 20% Leucaena leucocephala + 30% cassava. Variables observed in this study include meat protein content, meat fat, water content and collagen. The results of study showed that the meat protein content of male kacang goat received T1 treatment was higher (P <0.05) than the animals treatments of T0; while the animals that were treated with T0, T2 and T3 were relatively the same protein content. Conversely, the variables of meat fat, collagen and meat water content were relatively the same between treatments. It can be concluded that the use of milled corn as an energy source in male kacang goat can increase the meat protein content. However, the fat content, collagen, and water content of the meat have not shown significant differences between treatments.